An Asia That Can Say No - Malay Jr., Armando (Kasarinlan: Philippine Journal of Third World Studies; Vol 12 No 3 (1997): Rethinking the Third World, 2007)
Excerpt One of the more successful gimmicks that extreme Right wing leader Jean-Marie Le Pen deploys in his bid to legitimize racism as a political issue in France is the slogan, "He says out loud what others only think silently." Politically-correct sentiments can go hang; in the demagogues estimation, a fascistic counter-hegemony's time has come around at last. Le Pen's party, the National Front, has met phenomenal success in southeastern France, where some of that country's biggest immigrant populations are found; this may be taken to be a fair endorsement of his xenophobic discourse.